A Comparison of Video Performance Feedback and Self-Monitoring Strategies to Improve Pre-Service Teachers' Implementation of Systematic Instruction. (June 2023) - Lyon, Kristin Joannou; Walker, Virginia L.; Smith, Heather Haynes; Chen, Jie
Teacher preparation programs play an important role in preparing future special education teachers in the implementation of evidence-based interventions for students with disabilities. The purpose of this study was to examine the social validity and effects of two training strategies––video performance feedback and self-monitoring—on systematic instruction implementation of 51 pre-service special education teachers enrolled in a cross-categorical program. Systematic instruction implementation focused on two common response prompting systems––constant time delay and system of least prompts––across discrete and chained skills. Our findings indicate that, overall, both training strategies were effective in improving pre-service teachers' systematic instruction implementation. Across both training strategies and response prompting systems, there were significant gains in implementation when used to teach chained skills. Additionally, pre-service teachers found both training strategies effective and feasible. We present implications for teacher preparation and future research directions.